2022
DOI: 10.3390/polym14020286
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-Based Nanofibers Processing Techniques and Methods Based on Bottom-Up Approach—A Review

Abstract: In the past decades, cellulose (one of the most important natural polymers), in the form of nanofibers, has received special attention. The nanofibrous morphology may provide exceptional properties to materials due to the high aspect ratio and dimensions in the nanometer range of the nanofibers. The first feature may lead to important consequences in mechanical behavior if there exists a particular orientation of fibers. On the other hand, nano-sizes provide a high surface-to-volume ratio, which can have impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 174 publications
(202 reference statements)
0
16
0
Order By: Relevance
“…On the other hand, less guaiacol was detected in the extract solutions from CNF-CH or CNF-CDCH film, possibly due to two reasons: (1) smoke VPs were presented as bound forms although they were adsorbed and/or adsorbed, and (2) smoke VPs were blocked (neither adsorbed, nor absorbed to film). A previous study revealed that CH may interact with guaiacol smoke compounds via electrostatic interaction at low pH (Milhome et al, 2009) and hydrogen bonds (Hensley et al, 2016;Kramar & González-Benito, 2022). It was also assumed that the tight polymer-polymer network in CNF-CH and CNF-CDCH films could block guaiacol from interacting with the films since both hydroxyl and amine groups were unavailable to bind.…”
Section: Uv-vis Absorption Spectra Of Filmsmentioning
confidence: 99%
“…On the other hand, less guaiacol was detected in the extract solutions from CNF-CH or CNF-CDCH film, possibly due to two reasons: (1) smoke VPs were presented as bound forms although they were adsorbed and/or adsorbed, and (2) smoke VPs were blocked (neither adsorbed, nor absorbed to film). A previous study revealed that CH may interact with guaiacol smoke compounds via electrostatic interaction at low pH (Milhome et al, 2009) and hydrogen bonds (Hensley et al, 2016;Kramar & González-Benito, 2022). It was also assumed that the tight polymer-polymer network in CNF-CH and CNF-CDCH films could block guaiacol from interacting with the films since both hydroxyl and amine groups were unavailable to bind.…”
Section: Uv-vis Absorption Spectra Of Filmsmentioning
confidence: 99%
“…The CNF structure’s stability is enhanced by its crystalline character. When combined with other membrane materials having low crystallinity, CNF imparts stiffness and high strength to the nanocomposite membrane, thereby increasing water flux and antifouling in addition to the intrinsic properties [ 131 , 132 , 133 , 134 ]. In addition, CNFs are one of the best and cheapest options as they exhibit high-permeability, ultrahigh water flux, better hydrophilicity, and good salt rejection [ 135 ] when used in membranes.…”
Section: Cellulose Nanofibrils (Cnf): Structure Properties and Desali...mentioning
confidence: 99%
“…Highly porous structures with tunable pore sizes and shapes are sought-after in filtration applications. There is an increasing interest in the electrospinning of CA fibers . Ultrathin fibrous CA membranes compete with fossil-based commercial membranes in high-flux water filtration .…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing interest in the electrospinning of CA fibers. 10 Ultrathin fibrous CA membranes compete with fossil-based commercial membranes in high-flux water filtration. 11 Electrospun CA fibers were impregnated with hydroxyapatite nanoparticles as an environmentally friendly adsorption system for removing heavy metals from water.…”
Section: ■ Introductionmentioning
confidence: 99%